α7 Nicotinic Acetylcholine Receptor May Be a Pharmacological Target for Perioperative Neurocognitive Disorders - Wei, Penghui; Lyu, Wenyuan; Xu, Lin; Feng, Hao; Zhou, Haipeng; Li, Jianjun (Frontiers in Pharmacology, 2022)
Background: The α7 nicotinic acetylcholine receptor (α7nAChR) is a promising therapeutic target in neurodegenerative diseases. This study examined the effects of surgery and anesthesia on α7nAChR expression in the central nervous system and determined the mechanisms by which α7nAChR mediates neuroprotection in perioperative neurocognitive disorders (PNDs) in aged mice. Methods: Eighteen-month-old male C57BL/6J mice underwent aseptic laparotomy under isoflurane anesthesia, maintaining spontaneous ventilation to establish the PNDs model. Agonists and antagonists of the α7nAChR and tropomyosin receptor kinase B (TrkB) receptors were administered before anesthesia. The α7nAChR expression, peripheral as well as hippocampal interleukin-1β (IL-1β), and the brain-derived neurotrophic factor (BDNF) levels were assessed. Separate cohorts of aged mice were tested for cognitive decline using the Morris water maze (MWM). Results: Surgery and anesthesia significantly suppressed α7nAChR expression in the hippocampus and cortex. Surgery-induced IL-1β upregulation in the serum as well as hippocampus and hippocampal microglial activation were reversed by the α7nAChR agonist. A significant reduction in the hippocampal BDNF levels were also observed. The α7nAChR stimulation reversed, and α7nAChR suppression promoted BDNF reduction in the hippocampus. Blocking the BDNF/TrkB signaling pathway abolished α7nAChR-induced neuroprotection in PNDs, as evidenced by poor cognitive performance in the MWM test. Conclusions: These data reveal that α7nAChR plays a key role in PNDs. The mechanisms of the anti-inflammatory pathway and BDNF/TrkB signaling pathways are involved in α7nAChR-meidiated neuroprotection in PNDs.